2014
DOI: 10.1177/0363546513518417
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hip Pain in a Prospective Cohort of Asymptomatic Volunteers

Abstract: The presence of a cam deformity represents a significant risk factor for the development of hip pain. An elevated alpha angle at the 1:30 clock position and decreased internal rotation are associated with an increased risk of developing hip pain. However, not all patients with a cam deformity develop hip pain, and further research is needed to better define those at greater risk of developing degenerative symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 35 publications
2
60
0
1
Order By: Relevance
“…Several authors have shown that the severity of the cam deformity (that is, a higher alpha angle) is associated with an increased risk of hip pain and joint degeneration [7,28,33]. Typically, a cam deformity is indicated by an alpha angle greater than 50.5°and 60°in the oblique-axial and radial plane, respectively [7,36,37,39].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that the severity of the cam deformity (that is, a higher alpha angle) is associated with an increased risk of hip pain and joint degeneration [7,28,33]. Typically, a cam deformity is indicated by an alpha angle greater than 50.5°and 60°in the oblique-axial and radial plane, respectively [7,36,37,39].…”
Section: Introductionmentioning
confidence: 99%
“…The cam deformity, characterized by an aspherical femoral head-neck junction, has been suggested as a cause of labral-chondral damage as well as an early cause for hip osteoarthritis [11,17]. Several studies suggest that a severe cam deformity, as defined by larger alpha angles, could indicate which individuals may be at risk of developing early hip pain and arthritis [1,22]. Although many symptomatic individuals with a cam morphology experienced different hip kinematics, notably during level walking [21] and maximal squatting [23,24], other individuals with a cam morphology may not experience any clinical signs or symptoms [2,12,13,19,22,33,45].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that a severe cam deformity, as defined by larger alpha angles, could indicate which individuals may be at risk of developing early hip pain and arthritis [1,22]. Although many symptomatic individuals with a cam morphology experienced different hip kinematics, notably during level walking [21] and maximal squatting [23,24], other individuals with a cam morphology may not experience any clinical signs or symptoms [2,12,13,19,22,33,45]. In addition to elevated alpha angles, it was recently noted that a decreased femoral neckshaft angle might be indicative of early symptoms as well [13,33,34,45]; however, it is unclear what combined effects a large cam morphology and decreased femoral neck-shaft angle have on resultant hip stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Body pain diagrams, which have been used for more than 20 years in musculoskeletal pain research, provide a rapid and inexpensive way to measure the extent, distribution, and location of pain [14,18,21,24,28]. Widespread pain has been recognized as a poor prognostic factor in diseases such as rheumatoid arthritis, cancer, and chronic low back pain, and a poor prognostic factor for outcome of TKA [18,28].…”
Section: Introductionmentioning
confidence: 99%